Sustainable energy conversion for electricity and coproducts : principles, technologies, and equipment - Rao, Ashok D. (Hoboken : Wiley, 2015)
'Provides a comprehensive and a fundamental approach to the study of sustainable fuel conversion for the generation of electricity and for coproducing synthetic fuels and chemicals'--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Electric power production -- Energy conservation; Electric power-plants -- Equipment and supplies; Renewable energy sources; Fuel trade -- By-products.; Chemicals; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Electronic books